2007
DOI: 10.1093/hmg/ddl477
|View full text |Cite
|
Sign up to set email alerts
|

Increased longevity and refractoriness to Ca2+-dependent neurodegeneration in Surf1 knockout mice

Abstract: Leigh syndrome associated with cytochrome c oxidase (COX) deficiency is a mitochondrial disorder usually caused by mutations of SURF1, a gene encoding a putative COX assembly factor. We present here a Surf1-/- recombinant mouse obtained by inserting a loxP sequence in the open reading frame of the gene. The frequency of -/-, +/+ and +/- genotypes in newborn mice followed a mendelian distribution, indicating that the ablation of Surf1 is compatible with postnatal survival. The biochemical and assembly COX defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
232
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 276 publications
(245 citation statements)
references
References 39 publications
13
232
0
Order By: Relevance
“…In a paradoxical way, in yeast (Delaney et al., 2013), worms (Dillin et al., 2002), flies (Owusu‐Ansah, Song & Perrimon, 2013), and mice (Liu et al., 2005), suppression of mitochondrial ETC function increases lifespan (Dell'agnello et al., 2007; Durieux, Wolff & Dillin, 2011). While counterintuitive, these findings are supported by reports demonstrating that upregulation of mitochondrial stress response contributes to enhanced longevity in the long‐lived mitochondrial mutants (Durieux et al., 2011; Kirchman, Kim, Lai & Jazwinski, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a paradoxical way, in yeast (Delaney et al., 2013), worms (Dillin et al., 2002), flies (Owusu‐Ansah, Song & Perrimon, 2013), and mice (Liu et al., 2005), suppression of mitochondrial ETC function increases lifespan (Dell'agnello et al., 2007; Durieux, Wolff & Dillin, 2011). While counterintuitive, these findings are supported by reports demonstrating that upregulation of mitochondrial stress response contributes to enhanced longevity in the long‐lived mitochondrial mutants (Durieux et al., 2011; Kirchman, Kim, Lai & Jazwinski, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…RNAi knockdown of either UBL5 or DVE1 (mediators of mtUPR) reversed lifespan extension in both mutants. Similar to that, increased longevity by muscle‐specific disruption of ETC Complex I in Drosophila was dependent on mtUPR (Owusu‐Ansah et al., 2013), and Surf1 knockout mice deficient for ETC Complex IV had increased expression of mtUPR genes (Dell'agnello et al., 2007; Pulliam et al., 2014). It is important that, a number of other pro‐longevity models, such as NAD+/Sirtuin1 or rapamycin in C. elegans , also require mtUPR (Houtkooper et al., 2013; Owusu‐Ansah et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a study by Dell'agnello et al. (2007) reported that mice lacking expression of the Surf1 gene, which codes for the SURF1 assembly protein for complex IV (cytochrome c oxidase, COX) of the electron transport chain (Zhu et al., 1998), show a significant increase in mean lifespan despite a dramatic reduction in COX activity (Dell'agnello et al., 2007). These studies support the concept that mitochondrial function and lifespan are not causally linked.…”
Section: Introductionmentioning
confidence: 99%
“…Mice lacking active SURF1 protein ( Surf1 −/− mice) were developed to study Leigh Syndrome (Dell'agnello et al., 2007). However, despite reduced COX activity in all tissues, the Surf1 −/− mice exhibited an unexpected increase in lifespan and a number of phenotypes that do not seem consistent with reduced mitochondrial ETC activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation